Maintain or Improve Stored Hay Quality - Jeffrey N. Carter (EDIS, 2007)
AN173, a 2-page fact sheet by Jeffrey Carter, gives some tips for storing hay. Includes references and a table showing forage quality changes when stored in a barn or outside. Published by the UF Department of Animal Science, July 2007.